Hepatocellular Carcinoma: Self‐Activated Cascade‐Responsive Sorafenib and USP22 shRNA Co‐Delivery System for Synergetic Hepatocellular Carcinoma Therapy (Adv. Sci. 5/2021). Issue 5 (3rd March 2021) - Xu, Shengjun; Ling, Sunbin; Shan, Qiaonan; Ye, Qianwei; Zhan, Qifan; Jiang, Guangjiang; Zhuo, Jianyong; Pan, Binhua; Wen, Xue; Feng, Tingting; Lu, Haohao; Wei, Xuyong; et al.
Abstract : Resistance to sorafenib remains one of the biggest concerns for hepatocellular carcinoma treatment. In article number 2003042, Xiao Xu, Jiajia Xiang, and co‐workers developed a self‐activated sorafenib and USP22 shRNA codelivery nanoplatform (Gal‐SLP) to reverse cancer stemness and sensitive cancer cells to sorafenib. Gal‐SLP releases USP22 shRNA efficiently and enhances the intracellular sorafenib accumulation in cancer cells. Gal‐SLP exhibits potent antitumor efficiency in a sorafenibinsensitive patient‐derived xenograft (PDX) model.